Cardiac telerrehabilitation: a safe and effective alternative in patients with coronary artery disease. (11th May 2022) - Calvo-Lopez, M; Arranz, R; Marin, J; Gruosso, D; Falces-Salvador, C; Roque, M; Andrea, R; Vidal, B; Sitges, M; Sanz-De La Garza, M
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): Ferrer Internaciona Groupl, S.A Background: Center-based cardiac rehabilitation programs (CRP) have shown to reduce morbidity and mortality after an ischemic cardiac event, but their vastly underutilized. Home-based CRP seems to improve patient's adherence, but there is still scarce evidence, especially in elderly patients and women. Purpose: To develop a holistic home-based CRP for ischemic heart disease patients and evaluate its safety and impact on functional capacity, adherence to a heart-healthy lifestyle and quality of life. Methods: The 8-week home-based CRP will include 60 patients (50% women) with no age limit who have suffered an acute myocardial infarction in the previous 3 months, with LVEF ≥40% and a tablet/mobile device. The CRP (Picture 1) includes 3 weekly exercise sessions combining tailored aerobic and strength training and 1 weekly educational session focused on lifestyle habits, therapeutic adherence, and patient empowerment. Results: Between January and October 2021, 56 patients were included: 2 were rejected for presenting ventricular arrhythmias in the initial stress test and 4 due to technological barrier; 14 patients are currently performing the CRP. The preliminary results from the 36 patients who have completed the CRP show a significant increase in functional capacity, muscle strength, weekly training volume, adherence to Mediterranean diet, emotional state (anxiety) and quality of life (Picture 2). There have been no complications and patient's adherence has been excellent for both exercise (85%) and educational (80%) sessions. Conclusion: A holistic telematic CRP dedicated to patients after an ischemic cardiac event, including patients of both gender and of no age-limit, seems to be a feasible, safe and effective in improving maximal aerobic capacity, weekly training volume, muscle strength, quality of life, compliance with the Mediterranean diet and emotional state.